Mencari Bentuk Estetika Film Nasional melalui Wayang dalam Relief Candi-candi di Jawa - Prakosa, Gotot (Fakultas Film dan Televisi - Institut Kesenian Jakarta, 2009)
In Asia the concept of projecting moving pictures has been understood for at least a thousand years. The shadow theater so popular in those cultures conjured up gods and heroes, animals from fables, and demons on a screen and porta,ved them in various adventures. The earliest remnants of shadow' play were discovered in China and in Indonesia and stem from the 11 century. Two dimensional filigree figures were cut from tanned animal skins and artistically painted in color. The shadow players manipulated the chosen figure’s movable limbs with rods right up against the back of a screen of paper or silk. The light from an oil lamp illuminated the figure in such a way that the viewers could even enjoy the moving shadows in color. Especially in Indonesia, the shadow play Wayang Kulit is still popular today, and utilizes black silhouette figures and three-dimensional dolls along with the traditional audiences, ever mindful of tradition, still envision engineering the actual spirits of their ancestors in the moving enterplay of light and dark. This article tries to connect wav say wayang in comparison study with story film.